Clinical and Neuroimaging Findings of Cree Leukodystrophy: A Retrospective Case Series - Harder, S.; Gourgaris, A.; Frangou, E.; Hopp, K.; Huntsman, R.; Lowry, N.; Seshia, S.; Lemire, E.; Robinson, C.; Tynan, J. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: CLD is a rapidly progressive and invariably fatal neurodegenerative disorder. We describe clinical and neuroimaging findings in 5 infants with CLD. MATERIALS AND METHODS: Retrospective review of medical records of infants with CLD from the past 11 years at our institution was performed. Relevant clinical and demographic data were recorded. Specific attention was directed toward postmortem examination findings and genetic testing. CT and MR imaging results were reviewed. RESULTS: Five Cree infants were diagnosed with CLD. CT demonstrated bilateral symmetric hypoattenuation of the white matter and globus pallidus. MR imaging demonstrated corresponding T2 hyperintensity in these regions and abnormal signal intensity in the thalami and substantia nigra. Symmetric restricted diffusion in the deep white matter was seen. MRS demonstrated decreased NAA, elevated choline, and the presence of lactate. Postmortem examination in 1 infant showed corresponding poor myelination in the brain stem, cerebellum, deep gray structures, and the cerebral hemispheres. Genetic testing in 2 infants revealed homozygous mutations in the eIF2B5 gene. CONCLUSIONS: Neuroimaging in CLD is striking and is an important tool in diagnosing CLD. Extensive white matter involvement as well as involvement of the globus pallidus and patchy involvement of the thalami and substantia nigra are characteristic. MRS findings are compatible with destruction of normal brain parenchyma with evidence of anaerobic metabolism in the regions of demyelination. Clinical suspicion of VWM in a Native American infant from this region should prompt the consideration of CLD with appropriate imaging work-up and genetic testing. ADCapparent diffusion coefficientCACHchildhood ataxia with central hypomyelination syndromeChocholineCLDCree leukodystrophyCrcreatineDNAdeoxyribonucleic acidDWIdiffusion-weighted imagingeIF2eukaryotic translation initiation factoreIF2Beukaryotic initiation factor 2BeIF2B5eukaryotic initiation factor 2B subunit 5FLAIRfluid-attenuated inversion recoveryIVintravenousLaclactateMRIMR imagingMRSMR spectroscopyNAAN-acetylaspartatePRESSpoint-resolved spectroscopic sequenceRNAribonucleic acidVWMvanishing white matter disease